Curriculum Focus & Guidelines for Modification and Adaptation - Jamaica. Ministry of Education, Youth and Information (Ministry of Education, Youth and Information, Jamaica, 2020)
This document will be used by various stakeholders including school leaders, teachers and parents to streamline and simplify their workload while ensuring that all students have access to quality education that is informed by the national curriculum, regardless of the Education in Emergencies (EiE) Model that is adopted. It provides information regarding the required focus of the curriculum for selected subject areas and suggests modifications and adaptations at the school level for reaching all students. The alignment between curriculum and instruction will be helpful to teachers so that they can make better use of those practices that will help students to be meaningfully engaged, while enjoying the changes made to the teaching approach, scope of content and the environmental conditions for learning. To support efforts to plan for teaching and learning in the current context, the document presents guidelines for ascertaining the curriculum focus for various subject areas and recommendations for effective use of the formal curriculum to support teaching and learning. Specific information may be obtained about the following elements of the curriculum: The essential objectives to guide instruction (cognitive and other domains) The related content (skills, themes, strands etc.) for the objectives indicated Suggestions for ensuring alignment and appropriate modification of elements such as learning activities, assessment practices and learning resources are also included. It is expected that at the school level, modifications and adaptation strategies will be used to ensure that the EiE Model that is adopted is adequately catering for all students. Based on the diverse and dynamic nature of school contexts, modification of elements of the curriculum must be relevant to the current realities and in particular the profile (background, ability and affective characteristics) of the learners.
Keywords: curriculum framework; student development; Education in Emergencies